Ethical Commitment In Iranian Cinematic And Dramatic Art: A Semiological Study Of The Film Henas - abdelaziz, zineb (El Omda in Linguistics and Discourse Analysis, 2026)
This study investigates the manifestation of ethical commitment in Iranian cinema, positioning it as a distinct cultural phenomenon shaped by the ideological framework of the Islamic Revolution. Through a methodological approach integrating inductive reasoning, descriptive analysis, semiological examination, and critical analysis, the research examines Iranian cinema's transformation across pre- and post-revolutionary periods, exploring how ethical imperatives influence narrative structures, thematic elements, and production methodologies, mainly through state-imposed regulatory mechanisms. The findings demonstrate that Iranian cinema constitutes an innovative paradigm of ethically committed Islamic art. This paradigm has effectively reconciled ideological imperatives with artistic integrity, garnering international acclaim while maintaining indigenous cultural values. However, the study identifies substantial challenges, specifically mediating the tension between regulatory oversight and artistic expression in cinematic production.